2022
DOI: 10.1002/jbm.b.35174
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vitro and in vivo study of porcine‐ and bovine‐derived non‐cross‐linked collagen membranes

Abstract: The porcine-derived non-cross-linked collagen membrane Bio-gide ® (BG) and the bovine-derived non-cross-linked collagen membrane Heal-all ® (HA) were compared to better understand their in vitro biophysical characteristics and in vivo degradation patterns as a reference for clinical applications. It was showed that the porosity, specific surface area, pore volume and pore diameter of BG were larger than those of HA (64.5 ± 5.2% vs. 48.6 ± 6.1%; 18.6 ± 2.8 m 2 /g vs. 2.3 ± 0.6 m 2 /g; 0.114 ± 0.002 cm 3 /g vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(106 reference statements)
2
4
0
Order By: Relevance
“…A slowest resorption rate was observed with the pullulan/dextran-derived membranes compared to the commercial collagen membrane. This finding was also supported by previous studies reporting the tendency of collagen membranes to quickly resorb [43,[46][47][48]. A possible explanation is the progressive cellular infiltration observed inside the Bio-Gide ® membrane, whereas no cell infiltration was observed inside Mb and Mb + HA.…”
Section: Discussionsupporting
confidence: 89%
“…A slowest resorption rate was observed with the pullulan/dextran-derived membranes compared to the commercial collagen membrane. This finding was also supported by previous studies reporting the tendency of collagen membranes to quickly resorb [43,[46][47][48]. A possible explanation is the progressive cellular infiltration observed inside the Bio-Gide ® membrane, whereas no cell infiltration was observed inside Mb and Mb + HA.…”
Section: Discussionsupporting
confidence: 89%
“…In an in vitro test, Zhu et al observed a correlation between larger pore size and increased liquid absorption capacity and swelling behavior [ 26 ]. This could indicate a superior ability to absorb blood and tissue fluid, and thus, endogenous and added exogenous growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Swelling is another crucial parameter. A clinical correlation is believed to exist between a high swelling ratio and rapid resorption rate [ 26 ]. After implantation and suturing of the flap, the collagen materials are compressed to varying extents.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen stabilized scaffolds (coll-UV) and composite scaffolds (coll-PHNQ) demonstrated lower water uptake. This water uptake is indicative of scaffold responsiveness to aqueous environments, such as blood, with materials exhibiting high water holding capacity correlating positively with improved angiogenesis, beneficial for tissue regeneration 37 . Moreover, marine collagen, naturally enriched in glycosaminoglycans (GAGs), contributes to this water retention capability 38 .…”
Section: Amino Acidsmentioning
confidence: 99%